Machining composites : presented at the Winter Annual Meeting of the American Society of Mechanical Engineers, Chicago, Illinois, November 27-December 2, 1988 - American Society of Mechanical Engineers. Winter Meeting (1988 : Chicago, Ill.); Taya, Minoru; Ramulu, M. (Mamidala); American Society of Mechanical Engineers. Production Engineering Division; American Society of Mechanical Engineers. Materials Division (New York, NY : The Society)
163470